2020
DOI: 10.1093/ofid/ofaa306
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Coronavirus Disease 2019 Drive-Through Screening at an Academic Military Medical Center

Abstract: Drive-through COVID-19 screening can evaluate large numbers of patients while reducing healthcare exposures and personal protective equipment use. We describe the characteristics of screened individuals as well as drive-through process and outcome measures. Optimal drive-through screening involves rapid turnaround of test results and linkage to follow-up care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[ 7,8 ] Due to the scale of the COVID‐19 epidemic, an additional burden has been placed on traditional testing sites, such as hospitals, emergency rooms, and walk‐in clinics, thereby challenging their safety. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] Due to the scale of the COVID‐19 epidemic, an additional burden has been placed on traditional testing sites, such as hospitals, emergency rooms, and walk‐in clinics, thereby challenging their safety. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…One drive-through testing study calculated the test turnaround time, defined as the time between testing and communication of results. This was found to be 25 hours (IQR 21-29) in-house and 221 hours (IQR 161-269) if outsourced 25 .…”
Section: Resultsmentioning
confidence: 96%
“…In the UK, anecdotal evidence suggests that test results were communicated in 2-3 days (Vize, 2020), which is likely to have undermined tracing efforts considerably. In the US, one report of drive-through testing found that when outsourced, tests (n=476) were turned around in a median of 9.21 days (Lindholm et al 2020). Contact tracing may not be effective with such delays.…”
Section: Discussionmentioning
confidence: 99%